Il dramma dell’umiliazione: "La Merda" di Cristian Ceresoli e Silvia Gallerano, un successo internazionale (2010-2016) - Mariani, Laura (Mimesis Journal, 2016)
The Shit (La merda) by Cristian Ceresoli and Silvia Gallerano triumphed at the Edinburgh Fringe Festival and wowed the public all around the world. It shows how the theater, leaving the niches, can successfully challenge the dominant mass languages if it is based upon precise craftsmanship, the desire to «communicate» and the use of good practices in production, while an imponderable dose of artistic genius creates a special harmony with the times in which the authors live. At the core of the paper there are Cerasoli’s text – given its literary and theatrical value and also because of the problem of its translatability – and Gallerano’s interpretation. A ne example of «contemporary grotesque» thanks to a «vocal mask» which plays on the power of the face and on the nudity of the body, expressing the violence of the society of the spectacle through the tragedy of humiliation.